Lupus Erythematosus: Cutaneous Manifestations and Treatment - Alves, Francisca (2019)
Cutaneous lupus erythematosus (CLE) includes a broad range of dermatologic manifestations, which may or may not be associated with systemic manifestations. Specific CLE - defined by the presence of an interface dermatitis on histopathological evaluation - is divided into several sub-types, namely acute CLE (ACLE), subacute CLE (SCLE) and chronic CLE (CCLE). CCLE includes discoid lupus erythematosus (DLE), as well as other rarer forms such as LE profundus (LEP). Nonspecific skin findings, such as livedo reticularis or purpura are more frequently seen in patients with systemic disease. Diagnosis requires classification of the subtype, through a combination of physical examination, laboratory studies, histology and sometimes direct immunofluorescence, at the same time ensuring to exclude systemic disease. Regarding the treatment of CLE, antimalarials and topical steroids continue to be the standard of care; however, immunosuppressants, thalidomide analogs and monoclonal antibodies are possible systemic therapies for recalcitrant disease. Patient education on proper sun protection and avoidance of triggers is crucial. This paper reviews the clinical manifestations of CLE, as well as the treatment.